A formação continuada de professoras supervisoras do PIBID de Pedagogia: contribuições para ressignificação da profissionalidade docente - Nascimento, Edineia Gonçalves do (2021)
Studies carried out by Gatti and André (2010) and André (2015) show the relevance of PIBID as a space that promotes learning and the acquisition of professional knowledge. They corroborate the ideas of Nóvoa (2009) and Canário (2007) regarding the importance of teaching learning in the professional context and reaffirm the necessary articulation between university and school to improve the qualification of teaching and learning processes in basic education. It is in this context that this research is inserted, whose objective was to investigate the contributions of the Institutional Scholarship Program for Initiation to Teaching - PIBID of Pedagogy for the resignification, organization and planning of teaching action in the context of basic education. To this end, we opted for a qualitative approach that had the theoretical contribution of Lüdke and André (2008). Two supervisory professors working in the PIBID of Pedagogy at the Federal University of Lavras Minas – UFLA, members of the Program participated in the research. A literature review was initially carried out and, then, to establish the professional and personal profile of the participants, a questionnaire and interview were used as instruments for data collection. The results point to the contributions and expansion of learning in teaching and to the potentialization of innovations in pedagogical practices, with a view to redefining pedagogical action and teaching professionalism. It is considered, in light of the theoretical references studied and the analyzes carried out in this study, that the PIBID provided these future teachers with the expansion of knowledge, skills and perspectives of new forms of reflection about teaching and the pedagogical practice they performed. The research reaffirms the need to establish spaces, in the context of the school, for reflection on teaching action and moments of approximation between theory and practice, between teachers in training and teachers in continuing education, between the school and the University.